Egas Moniz: 90 Years (1927–2017) from Cerebral Angiography - Artico, Marco; Spoletini, Marialuisa; Fumagalli, Lorenzo; Biagioni, Francesca; Ryskalin, Larisa; Fornai, Francesco; Salvati, Maurizio; Frati, Alessandro; Pastore, Francesco Saverio; Taurone, Samanta (Frontiers in Neuroanatomy, 2017)
In June 2017 we celebrate the 90th anniversary of the pioneer discovery of cerebral angiography, the seminal imaging technique used for visualizing cerebral blood vessels and vascular alterations as well as other intracranial disorders. Egas Moniz (1874-1955) was the first to describe the use of this revolutionary technique which, until 1975 (when computed tomography, CT, scan was introduced in the clinical practice), was the sole diagnostic tool to provide an imaging of cerebral vessels and therefore alterations due to intracranial pathology. Moniz introduced in the clinical practice this fundamental and important diagnostic tool. The present contribution wishes to pay a tribute to the Portuguese neurosurgeon, who was also a distinguished neurologist and statesman. Despite his tremendous contribution in modern brain imaging, Egas Moniz was awarded the Nobel Prize in Physiology or Medicine in 1949 for prefrontal leucotomy, the neurosurgical intervention nowadays unacceptable, but should rather be remembered for his key contribution to modern brain imaging.